2001
DOI: 10.1128/jb.183.14.4227-4234.2001
|View full text |Cite
|
Sign up to set email alerts
|

PhcS Represses Gratuitous Expression of Phenol-Metabolizing Enzymes in Comamonas testosteroni R5

Abstract: We identified an open reading frame, designated phcS, downstream of the transcriptional activator gene (phcR) for the expression of multicomponent phenol hydroxylase (mPH) in Comamonas testosteroni R5. The deduced product of phcS was homologous to AphS of C. testosteroni TA441, which belongs to the GntR family of transcriptional regulators. The transformation of Pseudomonas aeruginosa PAO1c (phenol negative, catechol positive) with pROR502 containing phcR and the mPH genes conferred the ability to grow on phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…The dmpR gene itself is located directly upstream of and is divergently oriented from dmpK. A large number of highly similar regulators to DmpR have been found, which all control phenol degradation operons (Table 6) (8,153,158,177,229,249). A few other examples worth mentioning here are TbuT and TbmR, which control toluene monooxygenase gene expression in Burkholderia picketti PK01 (22) and Burkholderia sp.…”
Section: Catabolic Operons Controlled By Xylr/dmpr Subclass Regulatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The dmpR gene itself is located directly upstream of and is divergently oriented from dmpK. A large number of highly similar regulators to DmpR have been found, which all control phenol degradation operons (Table 6) (8,153,158,177,229,249). A few other examples worth mentioning here are TbuT and TbmR, which control toluene monooxygenase gene expression in Burkholderia picketti PK01 (22) and Burkholderia sp.…”
Section: Catabolic Operons Controlled By Xylr/dmpr Subclass Regulatorsmentioning
confidence: 99%
“…In the presence of the pathway substrate, repression is released by interaction of the regulator with the aromatic compounds or one of its metabolites (62,149,165,249). This was interpreted as a loss of DNA binding affinity mediated by the chemical inducer (see below) (62,165).…”
Section: Gntr-type Regulators Catabolic Operons Controlled By Gntr-tymentioning
confidence: 99%
See 2 more Smart Citations
“…This work (37) and an electrophoretic analysis in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (our unpublished data) indicated that the high activity of strain R5 was due to the high level of mPH expression, leading us to investigate its transcriptional mechanism. PhcR caused the expression of the mPH operon even in the absence of the genuine substrate for mPH, but this gratuitous expression was repressed by a member of the GntR family of transcriptional regulators named PhcS (38). This GntR family member for regulating the mPH operon has also been identified for C. testosteroni TA441.…”
mentioning
confidence: 95%